Elements of crimes under international law - Boas, Gideon (International criminal law practitioner library ;, 2008)
Volume II of the International Criminal Law Practitioner Library series focuses on core categories of international crimes: crimes against humanity, genocide, and war crimes. The authors present a comprehensive critical review of the law on the elements of these crimes and their underlying offenses, and examine how they interact with the forms of responsibility discussed in Volume I. They also consider the effect of the focus in early ICTY and ICTR proceedings on relatively low-level accused for the development of legal definitions that are sometimes ill-suited for leadership cases, where the accused had little or no physical involvement in the crimes. The book's main focus is the jurisprudence of the ad hoc Tribunals, but the approaches of the ICC and the various hybrid tribunals are also given significant attention. The relevant jurisprudence up to 1 December 2007 has been surveyed, making this a highly useful and timely work. Comprehensive review of jurisprudence, including key recent judgments and decisions, providing a one-stop reference tool on elements of crimes under international criminal law. Clarifies what can be a poorly defined and complicated area of law. Annex sets forth each element of the crimes under the jurisdiction of the ad hoc Tribunals, and sample combinations of crimes with each form of responsibility are provided, the first time this has been done--Publisher's description.